Análisis de seguridad de contenidos a través del estudio de vulnerabilidades, riesgos y mecanismos de protección para la transmisión de contenidos en sistemas de TDT, IPTV y OTT - Pazmiño Ortiz, Gabriel Alejandro (2026)
This research analyzes the security of audiovisual content in Digital Terrestrial Television (TDT), Internet Protocol Television (IPTV), and Over-The-Top (OTT) platforms in Ecuador through a documentary and non-experimental methodological approach. The study conducts a comparative examination of essential technical protection mechanisms, international security standards, and the national regulatory framework, with the objective of identifying vulnerabilities, protection gaps, and levels of normative compliance. To achieve this, evaluation matrices were developed using six core security mechanisms and eight national and international regulatory instruments, allowing the assessment of security alignment across the three technologies. The findings reveal substantial differences in security implementation. TDT exhibits the lowest protection level due to the absence of advanced mechanisms such as DRM, multifactor authentication, and IDS/IPS. IPTV shows an intermediate level, with partial adoption of mechanisms such as conditional access systems and basic encryption. In contrast, OTT platforms demonstrate the highest compliance level, resulting from the direct adoption of global digital security standards. The analysis also identifies significant regulatory gaps in Ecuador, particularly affecting TDT and IPTV, which stem from the lack of specific security requirements and insufficient technical oversight. In conclusion, the protection of audiovisual content in Ecuador is strongly influenced by both the technological architecture and the regulatory framework associated with each service. Strengthening national digital security policies is essential to guarantee the integrity and protection of transmitted content.